Peran Kearifan Lokal dalam Meningkatkan Kompetensi Literasi Bahasa Indonesia Siswa Sekolah Dasar - Saputra, Erwin Eka; Kasmawati, Kasmawati; Parisu, Chairan Zibar L. (Journal of Character and ELementary Education, 2025)
The decline in literacy rates of elementary school students in Indonesia is a major concern in the world of education. National Assessment data shows that Indonesian students' reading ability is still below average, and this challenge is exacerbated by the lack of contextual and relevant learning approaches for students. This article aims to analyze the role of local wisdom as a strategy in improving Indonesian language literacy competency in elementary school students through literature studies. Local wisdom as an expression of local community culture provides learning resources that are not only rich in moral and cultural values, but also in line with the context of students' lives. In this study, various scientific references are used to review the role of local culture-based learning media such as folklore, pantun, regional poetry, and traditional drama in shaping reading, writing, listening, and speaking skills. The results of the study show that the integration of local culture can provide a more meaningful learning experience, increase student motivation, and strengthen mastery of the Indonesian language. Through contextual learning that utilizes the richness of regional culture, students not only gain literacy skills, but also strengthen their cultural identity and the nation's noble values. Thus, a local wisdom-based approach is highly recommended as part of a literacy strengthening strategy in elementary schools.